Ovarian follicular responses to estrus and ovulation synchronization protocols in East African Shorthorn Zebu cattle - Patrick Mawadri; Tonny Balemwa; Denis Rwabiita Mugizi; Patrick Vudriko; Benon Mbabazi Kanyima; Charles Lagu; David Okello-Owiny; James Okwee-Acai; Maria Gorretti Nassuna-Musoke (Acta Veterinaria Scandinavica)
Abstract Background The East African Shorthorn Zebu (SHZ) is a Bos indicus breed adapted to tropical farming systems characterized by compromised feeding, welfare and harsh environments, contributing to poor reproductive performance. Estrus and ovulation synchronization protocols developed to enhance reproduction in Bos taurus have not achieved similar success in SHZ. This study evaluated effects of 7-day Co-synch + progesterone releasing intravaginal device (7-day Co-synch + P4ID; n = 17), Bee-Synch I (n = 17), and Bee-Synch II (n = 17) protocols on dominant follicle (DF) diameters, estrus and ovulation in 51 SHZ cows on extensive management. Estrus was monitored through observation and aids, while ultrasonography measured ovarian DF and corpus luteum (CL) diameters. Generalized linear models were used to compare means across protocols at 95% confidence level using R. Results DF diameters increased by 0.05 mm for every hour from P4ID withdrawal irrespective of protocol (P < 0.001). Mean DF diameters at P4ID withdrawal were 6.015 ± 0.903, 4.93 ± 0.737 and 7.31 ± 0.613 mm for 7-day Co-synch + P4ID, Bee synch I and Bee synch II respectively and the difference between Bee synch I and Bee synch II were significant (P.adj = 0.044). At last gonadotropin-releasing hormone (GnRH) administration time, DF diameters were 8.76 ± 0.725, 7.29 ± 0.505, and 9.68 ± 0.521 mm for 7-day Co-synch + P4ID, Bee synch I and Bee synch II respectively, with significant differences between Bee-Synch I and Bee-Synch II (P-adj = 0.016). Mean preovulatory DF diameters were 10.64 ± 0.333, 8.97 ± 0.335 and 10.30 ± 0.236 mm for the 7-day Co-synch + P4ID, Bee synch I and for Bee synch II respectively, with significant differences between Bee-synch I and 7-day Co-synch + P4ID (P.adj = 0.011) and between Bee-Synch I and Bee-Synch II (P.adj = 0.008). Estrus expression rates were not significantly different and 47%, 41.2% and 58.8% for 7-day Co-synch + P4ID, Bee synch I and Bee synch II respectively, while ovulation rates were 41.2%, 52.94% and 82.35% respectively. Mean ovulation times and last GnRH to ovulation intervals were significantly longer for both 7-day Co-synch + P4ID and Bee synch II than for Bee synch I. Conclusions Bee synch II and 7-day Co-synch + P4ID outperformed Bee synch I presenting opportunities for fertility improvement in SHZ. The results highlight the need for tailored fixed-time estrus and ovulation synchronization protocols to enhance fertility in B. indicus cattle under tropical conditions.